Don McKay and Metaphor: Stretching Language Toward Wilderness - Bushell, Kevin (Studies in Canadian Literature)

(untitled) (None, 1996)
One characteristic of Don McKay's poetry is his striking use of metaphor; it demands a heightened state of attention and imagination that serves to stretch language beyond the merely descriptive. In considering both post-structuralist and phenomenological approaches to metaphor and poetics, a survey of some of the poems from McKay's collections Birding, or desire and Night Field reveals McKay's views of language and poetry as similar to those of Heidegger. Further, McKay's metaphors are shown as both informing and being informed by the poems that contain them. The use of metaphor in McKay's poetry acts a springboard into what can be best described as wilderness. Metaphor, in these instances, can be considered analogous in many ways to nature poetry.